2013
DOI: 10.2754/avb201382040399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peroral supplementation of different forms of zinc on the ruminal mucosa of goat kids – a morphometric study

Abstract: The aim of the study was to identify the effect of supplementation of various forms of zinc on the ruminal mucosa and dimensions of ruminal papillae in 6-month-old goat kids. The experimental period lasted from weaning to slaughter (4 months). All 20 kids divided into four groups of five animals, were fed with the same feeding dose, which was different only in the quantity and form of zinc. Control group was without additional zinc supplementation (group A), the other groups were supplemented with zinc in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…5). The supplementation of cattle diets with zinc has long been studied to understand its impact on milk production and calf health [47]; however, its role in the early rumen development and the microbial modulation of this process are yet to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…5). The supplementation of cattle diets with zinc has long been studied to understand its impact on milk production and calf health [47]; however, its role in the early rumen development and the microbial modulation of this process are yet to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the metal ions copper, cadmium and magnesium can affect the activity of some rumen enzymes which play an important role in nitrogen metabolism, and may further change the nitrogen metabolism in the rumen of sheep [91]. Zinc absorption also plays an vital role in early rumen papillae development and keratinization in goats [92]. Ion, metal ion, and calcium ion binding are also indispensable molecular activities occurring throughout follicle growth in yaks [93].…”
Section: Discussionmentioning
confidence: 99%
“…Cellulolytic bacteria counts have also shown a decreasing trend with the increase in the ionic zinc levels in-vitro. In an interesting study by Černík [9], goats fed different organic and inorganic forms of zinc reported significant differences in the length, width and intensity of keratinisation of ruminal papillae. The kids supplemented with zinc in the form of zinc oxide had well developed papillae, reflecting the fact that some portion of zinc in the diet should necessarily be in inorganic form.…”
Section: Effect On Rumen Fermentationmentioning
confidence: 99%